0737 Factors Influencing Arousal Thresholds. (25th May 2022) - Prasad, Yashneel; Miller, Stuart
Abstract: Introduction: Obstructive Sleep Apnoea (OSA) is the most common sleep-related breathing disorder with an estimated prevalence of approximately 15-30 percent in males and 10-15 percent in females. A low respiratory arousal threshold (ArTH) is one of several traits involved in OSA pathogenesis. This has been shown to be reliably predicted using an Arousal Score which is calculated using the patients overall Apnoea-Hypopnoea Index (AHI), nadir SpO2 and Hypopnoea:Apnoea ratio where a score of 2 or more predicts a low arousal threshold, and a score of 1 indicates a high arousal threshold. Our objective was to describe factors associated with high arousal thresholds in patients with OSA as determined by the Arousal Score in a metropolitan population. Methods: 208 unselected, consecutive, adult, overnight polysomnography with prospectively calculated arousal scores were assessed from 2019 – 2020. Demographic and anthropometric data including Age, Sex, BMI, Epworth Sleepiness Score (ESS), AHI, SpO2 nadir, Hypopnoea:Apnoea ratio and arousal index was recorded. The arousal score was calculated by assigning one point for meeting each of the following requirements: AHI <30; SpO2 nadir > 82.8%; Hypopnoea:Apnoea ratio > 58.3, with a score <2 considered low. Spearmann correlation was performed to determine the factors associated with the Arousal Score. Results: 208 patients were included in the study. 35.6% of patients had mild sleep apnoea, 23.1% moderate sleep apnoea, 22.6% severe sleep apnoea with 18.8% of patients with no sleep apnoea. Mean arousal score was 2.47 (Std Dev 0.839). Spearman correlation indicated that disease severity, BMI (rs -.374, p-value < 0.01) and STOP-BANG (r2 -0.419, p-value < 0.01) had a statistically significant relationship with Arousal Score. That is, a higher AHI, BMI and STOP-BANG was associated with a low arousal score. Moreover, Gender and Epworth Sleepiness Score exhibited an insignificant association with arousal score. We found increasing severity of disease was associated with lower arousal score and therefore a higher arousal threshold Conclusion: Our study demonstrates that worsening sleep apnoea severity, higher BMI and higher STOP-BANG are associated with a lower arousal score and therefore higher arousal threshold. Gender and ESS do not appear to be significantly associated. Support (If Any):